THE SIGNIFICANCE OF THE LITHOSTRATIGRAFHIC POSITION AND THE TECTONIC DEFORMATION FOR THE LOCATION AND THE EXPLOITATION OF THE DOLOMITIC MARBLES OF FALACRON MOUNTAIN - Χατζηπαναγής, I.; Βουγιούκας, Δ. (Bulletin of the Geological Society of Greece, 2004)
At the broad area of Falakro mountain a systematic exploitation of dolomitic marbles is taking place. Besides, the fact that the excavated material consists of pure dolomitic carbonate, in the commerce there are more than 15 quality types with different denominations. The differences between them are related to their lithostratigraphic position and also with some structures of tectonic deformations. In the dolomitic marbles the following quality types are identified: The Aristo type, which consists of fine grained and white dolomitic rock. The Orion, Athina, Kalisto, Omega, Kyknos and Lambros Asteras which consist of white dolomitic material and thin coloured interbanding. The white Granitis, white Volakas and white Macedonia are composed of white dolomitic material with red interbanding which correspond to mylonites. Amvrossia is shaped by tectonic pseudoconglomerate material, while in Venus the dolomitic rock appears strongly folded. In the banded-cipoline marble series, quality types such as Dolit, Grey Lais and Pink Lais are identified, while in the Falakro type marble series, white Pirghon is identified.